Geochemistry of recent lacustrine sediments from Fildes Peninsula, King George Island, maritime Antarctica. Issue 5 (22nd April 2015) - Alfonso, Juan A.; Vasquez, Yaneth; Hernandez, Ana C.; Mora, Abrahan; Handt, Helga; Sira, Eloy
Abstract: Comprehensive geochemical analyses (bulk parameters, major and trace elements, organic matter, mineralogy and particle analysis) were carried out on sediments from seven lakes on Fildes Peninsula, King George Island. The resulting compositional dataset was subjected to principal component analysis and cluster analysis. The results showed that four different lacustrine sedimentary environments can be distinguished: i) lakes 1 and 2 with relatively high values of secondary aluminous clay minerals, ii) lake 4 with anthropogenic enrichment of Co, Cu and Zn, iii) lake 7 with relatively high values of Ba and P and a high zeolite content, and iv) all the other studied lakes. Our results indicate moderate chemical weathering in all lacustrine sediments and that the distance to the glacial ice margin is one of the most important factors influencing the chemical weathering in the area. Furthermore, depositional processes have little influence on the geochemistry of the investigated elements and that local bedrock is the main source of sediments in the lakes on Fildes Peninsula.